Macroeconomics and Stock Market Returns: A Case Study in the ASEAN Region 2018–2024 - Dwi Retno Sari; Selamet Riyadi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the impact of macroeconomic variables on stock market returns in the ASEAN region during the period 2018–2024. The macroeconomic variables examined include inflation rate, interest rate, and exchange rate, while stock market return is used as the dependent variable. The study focuses on four major ASEAN countries, namely Indonesia, Malaysia, Singapore, and Thailand, using monthly secondary data. A quantitative approach is employed using panel data regression analysis. Model selection is conducted through the Chow test, Hausman test, and Lagrange Multiplier test, which indicate that the Random Effect Model is the most appropriate. The results show that inflation, interest rate, and exchange rate simultaneously have a significant effect on stock market returns in the ASEAN region. Partially, inflation and interest rates have a negative and significant effect on stock market returns, while the exchange rate has no significant effect. These findings indicate that macroeconomic stability, particularly inflation control and interest rate policies, plays an important role in influencing stock market performance in ASEAN countries. This study is expected to provide valuable insights for investors, policymakers, and academics in understanding the relationship between macroeconomic variables and stock market returns in the ASEAN region.